2020
DOI: 10.1523/jneurosci.0763-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

HippoBellum: Acute Cerebellar Modulation Alters Hippocampal Dynamics and Function

Abstract: Here we examine what effects acute manipulation of the cerebellum, a canonically motor structure, can have on the hippocampus, a canonically cognitive structure. In male and female mice, acute perturbation of the cerebellar vermis (lobule 4/5) or simplex produced reliable and specific effects in hippocampal function at cellular, population, and behavioral levels, including evoked local field potentials, increased hippocampal cFos expression, and altered CA1 calcium event rate, amplitudes, and correlated activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 125 publications
(168 reference statements)
4
69
0
Order By: Relevance
“…In the last few years, several studies have further underscored the importance of the cerebellum in higher order function using acute, optogenetic manipulations of specific cell types. Acute activation of the cerebellar cortex disrupts hippocampal function and impairs performance in a spatial memory task [89], optogenetic activation and inhibition of Purkinje cells result in a reduction or increase in aggressive behaviors, respectively [90], and activation or inhibition of cerebellar fastigial nucleus neurons projecting to the periaqueductal gray modulate fear memories [91] (shown in Fig. 2).…”
Section: Disruptions In Cerebellar Function Lead To Social and Cognitive Deficits In Micementioning
confidence: 99%
“…In the last few years, several studies have further underscored the importance of the cerebellum in higher order function using acute, optogenetic manipulations of specific cell types. Acute activation of the cerebellar cortex disrupts hippocampal function and impairs performance in a spatial memory task [89], optogenetic activation and inhibition of Purkinje cells result in a reduction or increase in aggressive behaviors, respectively [90], and activation or inhibition of cerebellar fastigial nucleus neurons projecting to the periaqueductal gray modulate fear memories [91] (shown in Fig. 2).…”
Section: Disruptions In Cerebellar Function Lead To Social and Cognitive Deficits In Micementioning
confidence: 99%
“…The ability of the CB to derive a complex repertoire of non-motor functions from its relatively invariant cellular organization is largely attributed to its diverse outputs [35][36][37][38] . In addition to the heavily emphasized non-motor cerebellar influences on cortical regions [39][40][41][42][43][44][45] , functional and/or anatomical cerebellar connections with subcortical structures critical for cognition and emotion have also been documented 37,[46][47][48][49][50] . Here, we focused on the nucleus accumbens (NAc), a complex limbic structure that shares reward, motivation and affective functionality with the CB 51,52 .…”
Section: Introductionmentioning
confidence: 99%
“…Rather, there are particular pathway(s) -starting with the FN-CL output pathway --by which the cerebellum influences the hippocampus and hippocampal seizures. While a different pathway and/or output channel may be at play in healthy animals, it is worth noting that temporally precise modulation of hippocampal activity is observed with stimulation of cerebellar neurons in nonepileptic animals (Choe et al, 2018;Zeidler et al, 2020). Additionally, multisynaptic rabies tracing, following injections into the hippocampal dentate gyrus (again, in non-epileptic animals), results in labeling of neurons in the fastigial nucleus (Watson et al, 2019), futher supporting a (multisynaptic) connection between these structures.…”
Section: Discussionmentioning
confidence: 95%
“…Though canonically considered a motor control structure, mounting evidence indicates that the cerebellum is heavily involved in functions beyond this traditional framework (Schmahmann, 1996;Hilber et al, 1998;Leggio et al, 1999;Colombel et al, 2004;Popa et al, 2014;Yu and Krook-Magnuson, 2015;Schmahmann, 2019;Shipman and Green, 2019). Recent work has shown that the cerebellum can profoundly influence hippocampal function, with the ability to modulate hippocampal neuronal dynamics (Choe et al, 2018;Zeidler et al, 2020) and alter hippocampal-dependent behavior (Rochefort et al, 2011;Lefort et al, 2019;Zeidler et al, 2020). The influence of cerebellar dynamics on hippocampal function, in addition to being a topic of great scientific interest, has the potential to meet an urgent translational need in temporal lobe epilepsy (TLE), a disorder characterized by chronic, spontaneous seizures typically arising in the hippocampal formation.…”
Section: Introductionmentioning
confidence: 99%